2018
DOI: 10.1007/s10287-018-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

Un-diversifying during crises: Is it a good idea?

Abstract: High levels of correlation among fi nancial assets, as well as extreme losses, are typical during crisis periods. In such situations, quantitative asset allocation models are often not robust enough to deal with estimation errors and lead to identifying underperforming investment strategies.It is an open question if in such periods, it would be better to hold diversifi ed portfolios, such as the equally weighted, rather than investing in few selected assets. In this paper, we show that alternative strategies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…SL-LR is the strategy which takes a short position on LL and a long position on LR. might be combined with the recent findings of Giuzio and Paterlini (2019) and Bonaccolto and Paterlini (2020) to verify the benefits of diversification during distress periods.…”
Section: Implications For Portfolio Risk and Performancementioning
confidence: 93%
“…SL-LR is the strategy which takes a short position on LL and a long position on LR. might be combined with the recent findings of Giuzio and Paterlini (2019) and Bonaccolto and Paterlini (2020) to verify the benefits of diversification during distress periods.…”
Section: Implications For Portfolio Risk and Performancementioning
confidence: 93%
“…After falling slightly, the correlation increases again in 2012, during the European sovereign debt crisis. The correlation coefficient plays an important role for our following analysis, as increased positive correlation among the constituents is reported to reduce the effects of diversification (Choueifaty and Coignard 2008, You and Daigler 2010, Giuzio and Paterlini 2016. For all portfolios, the optimal weights vector,ŵ t , depends on the choice of the optimal λ parameter value.…”
Section: Sp500mentioning
confidence: 99%
“…Although, the RIDGE penalty stabilizes the mean-variance optimization, as it controls for multicollinearity, the shape of the penalty does not promote sparsity, leading to portfolios with an undesirably large number of active positions (Carrasco and Noumon 2012). Despite its appealing properties, the LASSO has reported shortcomings of (a) large biased coefficient values (Gasso et al 2010, Fastrich et al 2015, of (b) reduced recovery of sparse signals when applied to highly dependent data, like crisis periods (Giuzio and Paterlini 2016), and of (c) randomly selecting among equally correlated coefficients (Bondell and Reich 2008). Moreover, it is ineffective in presence of short selling (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Fastrich et al (2015) showed that sparse portfolios derived from penalized regression models provide improvements in terms of a lower concentration and turnover. Giuzio and Paterlini (2018) highlighted the positive impact of regularized models on the portfolio performance during stressed market conditions. Kremer et al (2018) used regularization techniques to minimize the risk in multi-factor portfolios.…”
mentioning
confidence: 98%